Pharmacokinetic and pharmacodynamic assessment of oral nicotinamide in the NEAT clinical trial for early Alzheimer’s disease - Gabriel L Ketron; Felix Grun; Joshua D Grill; Howard H Feldman; Robert A Rissman; Gregory J Brewer (Alzheimer’s Research & Therapy)
Abstract Background Nicotinamide, a form of B3 vitamin, is an NAD+ precursor that reduces pTau231 levels via histone deacetylase inhibition in murine models of Alzheimer’s disease (AD). A recent phase 2a randomized placebo-controlled trial tested high-dose oral nicotinamide for the treatment of early AD. While nicotinamide demonstrated good safety and tolerability, it did not significantly lower CSF pTau231, the primary biomarker endpoint of the study. Characterization of nicotinamide’s pharmacokinetics and metabolites in the blood and CSF is needed. Methods In these post hoc, blinded analyses of plasma and CSF samples from the completed two-site placebo controlled randomized trial testing of 1500 mg PO BID oral nicotinamide, we used mass spectroscopy to measure nicotinamide and its inactive metabolite 1-methyl-nicotinamide in plasma at baseline, 6, and 12 months and in CSF at baseline and 12 months from 23 participants on drug and 24 on placebo. Results Pharmacokinetic analysis found mean 12 month plasma nicotinamide increased > 130-fold to 52 μM while mean methyl-nicotinamide increased > 600-fold to 91 μM in individuals receiving nicotinamide compared to those receiving placebo, whose levels were unchanged from baseline. However, CSF nicotinamide was only measurable in 6 of the 19 available participants (32%) (mean increase of at least 147-fold to 18 μM). These CSF nicotinamide concentrations were 66% of their plasma levels, indicating good CNS bioavailability in only some participants. In contrast to CSF nicotinamide, more treated participants had higher CSF methyl-nicotinamide (n = 9, 43 μM), suggesting high-dosage nicotinamide was sufficient to pass the blood–brain barrier, but 13 of 19 were metabolically inactivated. Treatment favorably decreased mean pTau231 levels by 34% in those six participants with elevated CSF levels of nicotinamide, compared to 3% elevation in participants who did not have elevated CSF nicotinamide, and a 3% decrease for placebo. No such relationships were observed for total tau, pTau181, or amyloid beta biomarkers. Conclusions Our findings suggest that oral administration markedly increased mean plasma nicotinamide levels, however CSF levels were below quantitation in a majority of participants and there was extensive metabolic inactivation to methyl-nicotinamide. Both the bioavailability and rapid metabolic methylation need to be addressed if nicotinamide is further developed as a potential intervention for AD. Trial registration NCT03061474, last updated 2023–10-17. https://clinicaltrials.gov/study/NCT03061474 .